(untitled) (Journal of Energy and Safety Technology (JEST), 2024)
Occupational noise in hospital kitchens can significantly impact staff well-being due to prolonged exposure. This study evaluated noise levels in cooking, washing, and preparation areas of a hospital kitchen to assess compliance with the 2019 Noise Exposure Regulation and to understand how noise exposure varies by location and time. Measurements were conducted during peak hours during working activities showed that all areas were within the safe exposure limits, with the cooking area (77.620 dB) typically experiencing higher noise levels than the washing (76.338 dB) and preparation areas (75.302 dB). Noise levels significantly varied between peak and non-peak hours in the cooking and washing areas (p>0.05) but remained consistent in the preparation area (p=0.001). A weak yet significant positive correlation (p=0.001, r=0.145) was observed between noise levels and proximity to noise-generating distance of equipment, suggesting that reducing distance from noise sources may slightly increase exposure risks. These findings underline the need for ongoing monitoring and targeted noise reduction strategies in hospital kitchens to safeguard staff health, not hospital patients.